Analysis on the selection of course and institution of engineering students - Barros, David (2019)
Every year thousands of students apply for access to higher education in Portuguese universities. These students are allocated according to their application, secondary school grades and their preference to distinct establishment-course pairs. Despite official statistics provided by the Ministry of Science, Technology and Higher Education (MCTES), it is not always possible to have the relevant indicators for universities make a good decision concerning courses and vacancies to offer. This study evaluates the factors that influence students in their choice of a pair establishment-course as well as understand the different variables that are related to the same attribution of influence. The study is observational and empirical using questionnaires, with the appropriate statistical analysis. The results showed a relation in greater number among the studied factors and gender. In conclusion the prestige of the institution, employment and intellectual development are the factors most valued by students.